Faktor-Faktor Yang Mempengaruhi Income Smoothing Pada Perusahaan Manufaktur - Olivia Tamara, Herlin Tjundjung (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this empirical research is to examine the effect of financial leverage, firm age, profitability,andcash holdingtoward income smoothing in the manufacturing companies listed on the Indonesia Stock Exchange from 2015-2017. This research used 63 manufacturing companies that were selected using purposive sampling method for a total of 189 data in three years.In this study, the hypotheses test is performed using the logistic regression model. The results showed that the financial leverage, firm age, andprofitability have a significant negative effect on income smoothing, while cash holding do not have a significant effect on income smoothing